The plant kingdom: an exhaustible resource? - Heslop-Harrison, J.
It will be no news to this audience that the plant kindom is in serius trouble. The pressures now being placed upon vegetation are part ot the experience of all of us, for none here will be so young as not to be able to recall favorite woods, moors, field and shorelands now lost under advaneing city, road or wastle heaps.
Keywords: PLANT - CONSERVATION; ECOLOGY